Drug delivery strategies with lipid-based nanoparticles for Alzheimer’s disease treatment - Young-Ju Jang; Seong-Jun Kang; Hyun Su Park; Dong-Hyun Lee; Jae Hoon Kim; Ju-El Kim; Dong-Ik Kim; Chan-Hwa Chung; Jeong-Kee Yoon; Suk Ho Bhang (Journal of Nanobiotechnology)
Abstract Alzheimer's disease (AD) is a distinctive form of dementia characterized by age-related cognitive decline and memory impairment. A key hallmark of AD is the irreversible overaccumulation of beta-amyloid (Aβ) in the brain, associated with neuroinflammation and neuronal death. Although Aβ clearance and immunoregulation have been the major therapeutic strategies for AD, highly selective transport across the blood–brain barrier (BBB) negatively affects the delivery efficacy of the drugs without the ability to cross the BBB. In this review, we discuss the potential of lipid-based nanoparticles (LBNs) as promising vehicles for drug delivery in AD treatment. LBNs, composed of phospholipid mono- or bilayer, have attracted attention due to their exceptional cellular penetration capabilities and drug loading capabilities, which also facilitate cargo transcytosis across the BBB. Recent advances in the development and engineering of LBNs overcome the existing limitations of the current clinical approaches for AD treatment by addressing off-target effects and low therapeutic efficacy. Here, we review the transport pathways across the BBB, as well as various types of LBNs for AD therapy, including exosomes, liposomes, solid lipid nanoparticles (SLNs), and nanostructured lipid carriers (NLCs), to elucidate their distinctive properties, preparation methodologies, and therapeutic efficacy, thereby offering innovative avenues for novel drug development for clinical translation in AD therapy. Graphical Abstract